Implikasi Model Penilaian Kinerja Aparatur Terhadap Kualitas Pelayanan Publik - Hayat Hayat (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2016)
The purpose of this research is to find a public service performance appraisal model in order to improve the excellent and sustainable quality of public services from the aspects of service policy and service benefits for the community as users. The research design was carried out by surveying the research object, then conducting in-depth interviews to be analyzed in relation to the assessment of the performance of services that have been running to determine the feasibility of the research object. Diagnostic results are used as a sample for periodic testing through Focus Group Discussion (FGD) to produce performance appraisal instrument formulations and produce an assumptive model for service performance assessment. Implementation of performance appraisal using SKP is still running for 1 (one) year effectively, so it still requires adjustments and adaptations for employees in making SKP. The assessment process using SKP also requires assistance from superiors so that filling out SKP goes well. Each employee is required to fill out an SKP in which there is an assessment that must be filled in by each employee using a self-assessment system. The SKP assessment is also an obstacle for lower middle class employees who have to fill in the assessment independently, this is related to the level of education and the ability of employees to fill it out. Understanding of the rules and regulations for filling out SKP also makes it difficult for leaders to recapitulate the results of employee scores. This also has an impact on the performance of the leadership if the employee's SKP value is not balanced. So that there is still a thread that has not been unraveled in the performance appraisal policy using SKP which is considered to be less substantive. Fundamentally, performance evaluation must be proportional to the output produced by public service personnel in providing services to the community. Performance appraisal must be an indicator of quality public service processes. Good apparatus performance must have an impact on excellent service, so that it is integrated with the government's goals in the context of building bureaucratic reform to achieve good government.